Efektivitas berbagai jamu uyup-uyup terhadap sekresi air susu tikus (rattus norwegicus) menyusui= Effectiveness of VariousJamu Uyup-uyup on Milk Secretion of Lactating Rats (Rattus Norwegicus - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1988)
ABSTRACT The purpose of this experiment was to show the effect on milk secretion of female rats given jamu uyup-uyup (herbal medicine). There were 6 kinds of jamu uyup uyup tested from jamu factories and individuals. Female rats Mathis norwegicas) with their suckling progenies were used as testing animals. JAMU was given twice daily to each female rats directly via esophagus. There were two variation dosage that depend on weight. Suckling rats had been fasted for 6 hours and were separated from their mother. Then young rats were mixed with their mother again for 1,6 hours. The difference weight of young rats from the same nest, before and after sucklim was calculated as total milk secretion. The observation data was taken on the 5th, 8th 10th, 13'd and 1611 day. During this investigation, the normal growth and weight gain of each young rats in the same nest were weighed. The result showed that most of the jamu uyup-uyup promotes milk secretion of female rats significantly, and the highest average of milk secretion occured on 13rd day after delivery. The increase in milk secretion of each jamu uyup-uyup were not significant.